Navigating Family Relationships to Political Choice: The Role of the Head of Muslim Household as Agency - Hasan, Hamsah; Armin, Rizka Amelia; Adliyah, Nurul; Ulfa, Ulfa; Rusdi, Mikdar (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
In the context of family law, fathers play an essential role as the head of the family and the decision-maker who directs the family in various aspects, including decisions related to social and political interests. This study aims to describe the role of household heads as active agents in influencing family political choices. This research uses mixed methods to analyze the role of Muslim household heads in making political choices in the Luwu Raya region, South Sulawesi Province, Indonesia. Data were collected from 30 informants in the Luwu Raya regions using purposive sampling. Data in the form of interview documents, coded in several categories and then reduced according to the needs of the problem formulation. In addition to qualitative data, quantitative data percentages were also used to map political preferences, which were presented as diagrams. Finally, the data was narrated and interpreted to reach the right conclusion. The results show that the head of the family plays a role in shaping the political preferences of his family members by conducting more intense communication and persuasion. On the other hand, some family members have different political preferences due to their education and political experience.